2000
DOI: 10.12968/bjom.2000.8.7.8105
|View full text |Cite
|
Sign up to set email alerts
|

The implications of rest and sleep following childbirth

Abstract: The importance of sleep has been underestimated in nursing theory and practice (Southwell, 1995). Equally, its recognition as a priority in midwifery care has received only token lip service within the midwifery literature and profession. Although it is frequently identified as a need, there is little discussion as to the impact of insufficient rest and sleep or the role of the midwife in facilitating this need. The apparent mismatch between the reported occurrence of lack of rest and sleep and its relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…During their short stay of about two or three days in the hospital, first‐time parents have to learn everything from the relevant education provided by the hospital. However, factors such as insufficient psychological preparation, haste, physiological fatigue and other factors may prevent them from fully assimilating what they may want or need to learn (Larkin & Butler 2000, Driscoll 2002). In addition, not every pair of parents has access to adequate resources should they encounter care problems after the mother is discharged from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…During their short stay of about two or three days in the hospital, first‐time parents have to learn everything from the relevant education provided by the hospital. However, factors such as insufficient psychological preparation, haste, physiological fatigue and other factors may prevent them from fully assimilating what they may want or need to learn (Larkin & Butler 2000, Driscoll 2002). In addition, not every pair of parents has access to adequate resources should they encounter care problems after the mother is discharged from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Midwives are familiar with the tiredness and fatigue experienced by women after childbirth and in the months that follow, as they care for their babies and maintain their own lives with family and friends (Larkin & Butler 2000). The incidence of tiredness following childbirth has been recognized in the research literature for more than a decade (MacArthur et al .…”
Section: Tiredness and Fatigue In The Postnatal Periodmentioning
confidence: 99%
“…She found that babies breast‐feed more frequently and for longer during the night. Inevitably, women's sleep pattern is disturbed and the quality of sleep is impaired (Larkin & Butler 2000).…”
Section: Tiredness and Fatigue In The Postnatal Periodmentioning
confidence: 99%